Resolved nuclear kinematics link the formation and growth of nuclear star clusters with the evolution of their early- and late-type hosts - Pinna, F; Neumayer, N; Seth, A; Emsellem, E; Nguyen, DD; Boker, T; Cappellari, M; McDermid, RM; Voggel, K; Walcher, CJ (American Astronomical Society, 2021)
We present parsec-scale kinematics of 11 nearby galactic nuclei, derived from adaptive-optics assisted integral-field spectroscopy at (near-infrared) CO band-head wavelengths. We focus our analysis on the balance between ordered rotation and random motions, which can provide insights into the dominant formation mechanism of nuclear star clusters (NSCs). We divide our target sample into late- and early-type galaxies, and discuss the nuclear kinematics of the two subsamples, aiming at probing any link between NSC formation and host galaxy evolution. The results suggest that the dominant formation mechanism of NSCs is indeed affected by the different evolutionary paths of their hosts across the Hubble sequence. More specifically, nuclear regions in late-type galaxies are on average more rotation dominated, and the formation of nuclear stellar structures is potentially linked to the presence of gas funneled to the center. Early-type galaxies, in contrast, tend to display slowly rotating NSCs with lower ellipticity. However, some exceptions suggest that in specific cases, early-type hosts can form NSCs in a way similar to spirals.